Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Certainly! Let me provide a detailed, step-by-step solution to this problem.
We have a system of linear equations:
[tex]\[ \begin{array}{l} m + n = 7 \quad \text{(Equation 1)} \\ 2m - 3n = 4 \quad \text{(Equation 2)} \end{array} \][/tex]
To solve for [tex]\(m\)[/tex] and [tex]\(n\)[/tex], we can use either the substitution method or the elimination method. Here, we'll use the substitution method.
### Step 1: Solve one of the equations for one variable
From Equation 1, we can solve for [tex]\(m\)[/tex]:
[tex]\[ m + n = 7 \][/tex]
[tex]\[ m = 7 - n \][/tex]
### Step 2: Substitute the expression obtained into the other equation
Now, substitute [tex]\(m = 7 - n\)[/tex] into Equation 2:
[tex]\[ 2m - 3n = 4 \][/tex]
[tex]\[ 2(7 - n) - 3n = 4 \][/tex]
[tex]\[ 14 - 2n - 3n = 4 \][/tex]
[tex]\[ 14 - 5n = 4 \][/tex]
### Step 3: Solve for the variable
Isolate [tex]\(n\)[/tex]:
[tex]\[ 14 - 4 = 5n \][/tex]
[tex]\[ 10 = 5n \][/tex]
[tex]\[ n = \frac{10}{5} \][/tex]
[tex]\[ n = 2 \][/tex]
### Step 4: Substitute back to find the other variable
Now that we have [tex]\(n = 2\)[/tex], substitute it back into the expression for [tex]\(m\)[/tex] from Step 1:
[tex]\[ m = 7 - n \][/tex]
[tex]\[ m = 7 - 2 \][/tex]
[tex]\[ m = 5 \][/tex]
### Step 5: Calculate [tex]\(m - n\)[/tex]
To find the value of [tex]\(m - n\)[/tex]:
[tex]\[ m - n = 5 - 2 \][/tex]
[tex]\[ m - n = 3 \][/tex]
So, the value of [tex]\(m - n\)[/tex] is [tex]\( \boxed{3} \)[/tex].
We have a system of linear equations:
[tex]\[ \begin{array}{l} m + n = 7 \quad \text{(Equation 1)} \\ 2m - 3n = 4 \quad \text{(Equation 2)} \end{array} \][/tex]
To solve for [tex]\(m\)[/tex] and [tex]\(n\)[/tex], we can use either the substitution method or the elimination method. Here, we'll use the substitution method.
### Step 1: Solve one of the equations for one variable
From Equation 1, we can solve for [tex]\(m\)[/tex]:
[tex]\[ m + n = 7 \][/tex]
[tex]\[ m = 7 - n \][/tex]
### Step 2: Substitute the expression obtained into the other equation
Now, substitute [tex]\(m = 7 - n\)[/tex] into Equation 2:
[tex]\[ 2m - 3n = 4 \][/tex]
[tex]\[ 2(7 - n) - 3n = 4 \][/tex]
[tex]\[ 14 - 2n - 3n = 4 \][/tex]
[tex]\[ 14 - 5n = 4 \][/tex]
### Step 3: Solve for the variable
Isolate [tex]\(n\)[/tex]:
[tex]\[ 14 - 4 = 5n \][/tex]
[tex]\[ 10 = 5n \][/tex]
[tex]\[ n = \frac{10}{5} \][/tex]
[tex]\[ n = 2 \][/tex]
### Step 4: Substitute back to find the other variable
Now that we have [tex]\(n = 2\)[/tex], substitute it back into the expression for [tex]\(m\)[/tex] from Step 1:
[tex]\[ m = 7 - n \][/tex]
[tex]\[ m = 7 - 2 \][/tex]
[tex]\[ m = 5 \][/tex]
### Step 5: Calculate [tex]\(m - n\)[/tex]
To find the value of [tex]\(m - n\)[/tex]:
[tex]\[ m - n = 5 - 2 \][/tex]
[tex]\[ m - n = 3 \][/tex]
So, the value of [tex]\(m - n\)[/tex] is [tex]\( \boxed{3} \)[/tex].
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.